2020
DOI: 10.1016/j.ejvs.2020.04.029
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Operative Volume and Peri-operative Mortality After Non-elective Aortic Aneurysm Repair in Australia

Abstract: WHAT THIS PAPER ADDSThis study is the first to have examined the effect of hospital and surgeon operative volume on mortality after nonelective aortic aneurysm repair in Australia. It was found that higher volume hospital caseload reduced mortality after open surgical aortic aneurysm repair, particularly in the emergency subgroup compared with the semi-urgent. These findings are consistent with studies from the UK and North America. There was no significant association between surgeon or hospital volume and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Their results revealed an inverse relationship between the overall hospital caseload but not the individual surgeon's caseload and perioperative mortality in the context of non-elective AAA repair. Of interest, the effect was observed within the emergency OR group, while the authors did not observe a volume-related mortality association in the case of EVAR [23]. Similar experiences have been reported by others; however, the survival benefit of centralised treatment of OR for rAAA was found to be particularly dependent on the positioning of the proximal clamp and vanished when controlled for this parameter [24].…”
Section: Discussionsupporting
confidence: 64%
“…Their results revealed an inverse relationship between the overall hospital caseload but not the individual surgeon's caseload and perioperative mortality in the context of non-elective AAA repair. Of interest, the effect was observed within the emergency OR group, while the authors did not observe a volume-related mortality association in the case of EVAR [23]. Similar experiences have been reported by others; however, the survival benefit of centralised treatment of OR for rAAA was found to be particularly dependent on the positioning of the proximal clamp and vanished when controlled for this parameter [24].…”
Section: Discussionsupporting
confidence: 64%
“…Numerous studies have established a link between surgeon volume of open aortic surgery and improved patient outcomes. [24][25][26][27] Geiger et al, in a recent analysis, identified that performing a minimum of seven open aortic procedures annually was a standalone predictor of better outcomes following OAR. 27 Our study demonstrated a significant decline in open procedures over the past two decades.…”
mentioning
confidence: 99%